Strong, Recent Selective Sweeps Reshape Genetic Diversity in Freshwater Bivalve Megalonaias nervosa. (4th February 2023) - Rogers, Rebekah L; Grizzard, Stephanie L; Garner, Jeffrey T
Abstract: Freshwater Unionid bivalves have recently faced ecological upheaval through pollution, barriers to dispersal, harvesting, and changes in fish–host prevalence. Currently, over 70% of species in North America are threatened, endangered or extinct. To characterize the genetic response to recent selective pressures, we collected population genetic data for one successful bivalve species, Megalonaias nervosa . We identify megabase-sized regions that are nearly monomorphic across the population, signals of strong, recent selection reshaping diversity across 73 Mb total. These signatures of selection are greater than is commonly seen in population genetic models. We observe 102 duplicate genes with high d N /d S on terminal branches among regions with sweeps, suggesting that gene duplication is a causative mechanism of recent adaptation in M. nervosa . Genes in sweeps reflect functional classes important for Unionid survival, including anticoagulation genes important for fish host parasitization, detox genes, mitochondria management, and shell formation. We identify sweeps in regions with no known functional impacts, suggesting mechanisms of adaptation that deserve greater attention in future work on species survival. In contrast, polymorphic transposable elements (TEs) appear to be detrimental and underrepresented among regions with sweeps. TE site frequency spectra are skewed toward singleton variants, and TEs among regions with sweeps are present at low frequency. Our work suggests that duplicate genes are an essential source of genetic novelty that has helped this species succeed in environments where others have struggled. These results suggest that gene duplications deserve greater attention in non-model population genomics, especially in species that have recently faced sudden environmental challenges.